Pengaruh Kualitas Interaksi, Kualitas Lingkungan Fisik Dan Kualitas Hasil Terhadap Kepuasan Pengguna Layanan Pemerintah Pada Bagian Umum Sekretariat Daerah Kabupaten Gorontalo - Nismawaty S. Pahrun; Deby R. Karundeng; Moh. Afan Suyanto (Pusdikra Publishing, 2023)
The purpose of this study was to analyze the effect of the quality of interaction, the quality of the physical environment and the quality of the results on the satisfaction of users of government services at the General Section of the Regional Secretariat of Gorontalo Regency. Data analysis in this study used multiple linear regression analysis. The results showed that (1) the quality of interaction had a positive and significant effect on service user satisfaction, (2) the quality of the physical environment had a positive and significant effect on service user satisfaction, (3) the quality of results had a positive and insignificant effect on service user satisfaction, and ( 4) The quality of the interaction, the quality of the physical environment, and the quality of the results together have a positive and significant effect on the satisfaction of users of government services at the General Section of the Regional Secretariat of Gorontalo Regency.